The Joy of Water or Caring for Grandmother Lake in Atitlán, Guatemala - Celigueta Comerma, Gemma (2026)
This article explores the spiritual, ecological, and political relationship that the Tz'utujil Maya people of San Pedro La Laguna have with Lake Atitlán, which they consider to be a living being: Qatee Ya' (our mother lake). This relationship is manifested in daily practices, rituals, and dreams, and translates into concrete actions of care, such as those carried out by the “Guardians of the Lake,” groups of women who clean its shores. The text analyzes how this Mayan representation challenges technocratic and extractivist visions, proposing instead a “cosmopolitics” that integrates both ancestral and scientific knowledge. Through ethnographic description, it shows how caring for the lake becomes both a form of territorial defense and cultural resistance.